Implementasi Peraturan Bupati Bangli Nomor 29 Tahun 2018 Terhadap Pengelolaan Sampah Rumah Tangga di Desa Penglipuran Kabupaten Bangli - Putu Galang Widiantara Ws; Ida Ayu Putu Widiati; I Nyoman Sutama (Jurnal Interpretasi Hukum, 2022)
The implementation of Bangli Regent Regulation No. 29 of 2018 on Household Waste Management in Penglipuran Village, Bangli Regency is not optimal, as a result of various rapid changes, in terms of social, economic, political, tourism and cultural life. This study uses empirical research methods, namely by collecting data through observation and interviews to the research location. The results of this study found that the implementation of this Regent's Regulation was very good, but the role of the government was slightly causing the emergence of obstacles that caused the implementation of the Regent's Regulation itself to be less than optimal. However, there are also efforts that have been made by the Bangli Regency Government in the form of internal efforts, namely efforts from the Penglipuran Traditional Village and external efforts, namely efforts originating from outside the Penglipuran Traditional Village.